Characterising processes at sand-pile interface using digital image analysis and X-ray CT. Issue 4 (30th April 2019) - Doreau-Malioche, J.; Galvis-Castro, A.; Tovar-Valencia, R.; Viggiani, G.; Combe, G.; Prezzi, M.; Salgado, R.
Abstract : This paper presents the results of a tensile and a compressive load tests on an instrumented model pile pre-installed in medium–dense sand samples prepared in a half-circular calibration chamber with viewing windows along its symmetry plane. Digital image correlation (DIC) is used to obtain the displacement and strain fields in the sand surrounding the pile during and after loading. The orientation of the principal strains in the soil in the vicinity of the pile depends on the loading direction. To complement the description of sand-pile interface provided by DIC, a study is conducted at a smaller scale for the analysis of intergranular contacts. After loading, resin-cemented specimens are recovered from the vicinity of the pile and investigated at the grain scale by means of X-ray computed tomography. Novel qualitative results show the spatial evolution of contacts orientations for both tests. The two advanced image-based techniques used in this study give access to valuable micro-scale information and could be combined to better understand the deformation mechanisms driving the macroscopic response of non-displacement piles.